Quantum dot (Aun/Agn, n=3-8) capped single lipids: interactions and physicochemical properties - Maneri, Asma H. H.; Varode, Shruti Suhas; Maibam, Ashakiran; Ranjan, Priyatosh; Krishnamurty, Sailaja; Joshi, Krati (Physical Chemistry Chemical Physics, 2023)
Realizing the potential of nano-hybrid biomaterials in various applications (nanoprobes to drug delivery), special attention has been devoted towards their synthesis and development. Nonetheless, several questions pertaining to the interface chemistry between the constituent entities (biomolecules and organic/inorganic part) of these hybrids, still remain unresolved. Keeping these unsolved issues in mind, the present theoretical investigation focuses on determining the electronic/physicochemical properties and interactions within gold and silver quantum dot-capped single lipid molecules. Quantum dots of varying sizes and shapes have been chosen and then coupled with lipid molecules (1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC), 1,2-dimyristoyl-sn-glycero-3-phosphoethanolamine (DMPE), 1,2-dimyristoyl-sn-glycero-3-phosphoglycerol, sodium salt (DMPG)), at the choline/glycerol, carboxylate and phosphate site. It has been identified that Au Qds interact strongly as compared to Ag clusters. In addition to the type, the shape and size of the Qd also influences their attachment with lipids. Among various sites, the phosphate site provides a considerably stronger platform for the coupling of Qds. On the other hand, attachment at the choline site leads to significantly lower interaction energies. The trend noted in interaction energies coincides with the structure-electronic property analysis (interatomic bond distances, charge transfer, PO2- stretching frequencies), which further helps in deducing the nature of interactions. The molecular dynamics simulations performed on selected Qd-lipid complexes established that the Qd interacting with lipids at the phosphate site remains fairly stable at room temperature without undergoing fragmentation into individual components. On the other hand, at the choline site, the Qd-to-lipid coupling is unstable and therefore they experience disintegration at 300 K temperature. Additionally, a unique glycerol-to-phosphate site crossover is evidenced, which reaffirms that the phosphate site is selectively preferred by Qds for binding with lipid molecules.